Modified carbon paper substrate and gas diffusion electrode
The modified carbon paper substrate addresses hydrophobic agent-induced performance issues by creating a stable, hydrophobic interface for gas diffusion electrodes, ensuring catalyst activity and preventing leakage, suitable for electrolytic cells and batteries.
Patent Information
- Application Number
- CN202411167417.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-01-03
AI Technical Summary
Existing gas diffusion electrodes face issues with hydrophobic agents inhibiting electrochemical activity and stability due to excessive use, which affects catalyst performance and leads to gas and liquid leakage.
A modified carbon paper substrate is prepared by loading a fluorosilane-based modifier on carbon paper, creating a hydrophobic interface that maintains catalyst activity and stability, using a method involving mixing organic solvents, bases, and ultrasonication to form a solution, followed by loading catalyst materials.
The modified carbon paper substrate enhances gas diffusion electrode stability and maintains catalyst activity, reducing binder use and preventing leakage, with improved hydrophobicity and sustained performance under high current densities.
Smart Images

Figure CN119243204A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional materials, and in particular relates to a modified carbon paper substrate and a gas diffusion electrode. Background Art
[0002] Gas diffusion electrode (GDE) is a porous membrane electrode that allows a large amount of gas to diffuse from one side of the electrode and contact the catalyst, while the electrolyte solution connects the circuit with the catalyst from the other side of the electrode, effectively forming a solid-liquid-gas three-phase interface, and effectively improving the mass transfer rate of the electrolytic reactants. Commonly used gas diffusion electrodes use hydrophobic polymer materials (such as polytetrafluoroethylene, etc.) as hydrophobic agents for electrode materials, naphthol as a binder, and hydrophobic carbon paper as a conductive substrate. The use of hydrophobic agents plays an important role in constructing hydrophobic interfaces and preventing gas and liquid leakage from electrodes. The amount of materials used has an important influence on electrode performance. When the amount is too low, the electrode stability is difficult to ensure. When the amount is too high, the catalyst is covered and the activity is seriously reduced.
[0003] CN112875811A, the method uses titanium-based metal oxide coating as anode, metal mesh as substrate, modified waste tire carbon and hydrophobic modifier (polytetrafluoroethylene, polyvinylidene fluoride) to make electrode catalyst layer to construct an electrocatalytic oxidation reactor and use it in sewage treatment process. This method is mainly used in the field of waste tire recycling, and the electrode performance prepared by modified waste tire carbon is still inferior to commercial carbon materials. A 2-ethylanthraquinone modified gas diffusion electrode and its preparation method, CN101774666A, this invention is through the graphitized Vulcan 72 carbon black, isopropanol and polytetrafluoroethylene emulsion are prepared into a slurry, and applied on the hydrophobic carbon cloth as a gas diffusion layer, and the hydrophobic carbon cloth is also used as a current collector; then the catalytic layer is coated on the carbon black side of the gas diffusion layer, and the catalytic layer is a slurry prepared by a mixed solution of 2-ethylanthraquinone, Vulcan 72 carbon black, polytetrafluoroethylene emulsion, isopropanol and deionized water. This method uses graphitized carbon black to assist polytetrafluoroethylene emulsion to hydrophobically modify carbon cloth and catalyst. The treatment process includes a high-temperature annealing step, and the broadening of the catalyst is limited. At the same time, polytetrafluoroethylene will cover the catalyst and affect the electrocatalytic performance. Summary of the invention
[0004] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a modified carbon paper substrate and a gas diffusion electrode. The present invention overcomes the technical problem that the prior art hydrophobic agent has an inhibitory effect on the electrochemical activity.
[0005] The present invention provides a method for preparing modified carbon paper, comprising:
[0006] (1) mixing water and an organic solvent, adding a base to adjust the pH value, stirring, and then adding ethyl silicate, stirring to obtain a solution A;
[0007] (2) mixing dopamine hydrochloride and Tris-HCl buffer, ultrasonicating and stirring to obtain solution B;
[0008] (3) mixing solution A and solution B, then adding fluorosilane or perfluorocarboxylic acid, stirring, and ultrasonicating to obtain a modifier;
[0009] (4) Loading the modifier on carbon paper and drying it to obtain modified carbon paper.
[0010] Preferably, the organic solvent in step (1) is one or more of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, halogenated hydrocarbons, alcohols, ethers, esters, and ketones; wherein the aromatic hydrocarbon organic solvent includes one or more of benzene, toluene, and xylene; the aliphatic hydrocarbon organic solvent includes one or more of pentane, hexane, and octane; the alicyclic hydrocarbon organic solvent includes one or more of cyclohexane, cyclohexanone, toluene, and cyclohexanone; the halogenated hydrocarbon organic solvent includes one or more of chlorobenzene, dichlorobenzene, and dichloromethane; the alcohol organic solvent includes one or more of methanol, ethanol, and isopropanol; The ether organic solvent includes one or more of ether and propylene oxide; the ester organic solvent includes one or more of methyl acetate, ethyl acetate, and propyl acetate; the ketone organic solvent includes one or more of acetone, methyl butyl ketone, and methyl isobutyl ketone; the alkali is at least one of sodium hydroxide and ammonia water, wherein the concentration of sodium hydroxide is 0.3%-0.4% (mass fraction) and the concentration of ammonia water is 25-28% (volume fraction); the volume ratio of water, organic solvent, and tetraethyl orthosilicate is (10-20):(50-90):(3-5); the water is ultrapure water or deionized water.
[0011] Preferably, in step (1), alkali is added to adjust the pH value, ultrasonic dispersion is performed for 10-20 min, stirring is performed at 10-35° C. for 10-20 min, and then ethyl silicate is added, ultrasonic dispersion is performed for 0.5-1 h, and stirring is performed at 10-35° C. for 3-8 h.
[0012] The Tris-HCl buffer is prepared by completely dissolving tris(hydroxymethyl)aminomethane in water and adding concentrated hydrochloric acid to adjust the pH to 7.8-9 to obtain a Tris-HCl buffer;
[0013] Preferably, in step (2), the mass volume ratio of dopamine hydrochloride and Tris-HCl buffer is (10-200 mg): 50 mL; the pH of the Tris-HCl buffer is 7.8-9;
[0014] Preferably, the ultrasonic time in step (2) is 1-5 min; and the stirring is stirring at room temperature for 8-12 h.
[0015] Preferably, in step (3), the volume ratio of solution A to solution B is 0.1-(3:1); the fluorosilane is one or more of perfluorooctyltrimethylsilane, 1H, 1H, 2H, 2H perfluorododecyltriethoxysilane, tridecafluorooctylsilane, heptadecafluorodecylsilane; the perfluorocarboxylic acid includes one or more of perfluorobutyric acid, perfluoropentanoic acid, perfluorohexanoic acid, perfluoroheptanoic acid, and perfluorooctanoic acid. The volume ratio of the fluorosilane or perfluorocarboxylic acid to ethyl orthosilicate is 1:(1-3).
[0016] Preferably, in step (3), solution A and solution B are mixed and stirred at 10-35° C. for 5-15 hours;
[0017] Preferably, after adding fluorosilane in step (3), stirring is performed at 10-35° C. for 5-12 h, and the ultrasonic time is 20-40 min.
[0018] Preferably, the loading method in step (4) is at least one of drop coating, spin coating and spraying; the loading amount of the modifier on the carbon paper is 0.1-30 μL / cm 2 .
[0019] The invention provides a gas diffusion electrode, which comprises a modified carbon paper with a modifier loaded on one side, and a catalyst material loaded on the modified carbon paper.
[0020] Preferably, the catalyst material is a metal-based catalyst, including metals such as copper, gold, silver, zinc, platinum and their compounds; a non-metal-based catalyst, including a catalyst that does not contain metal, including proteins, small molecule catalysts, etc. The catalyst material loading is 0.1-30 mg / cm 2 .
[0021] The gas diffusion agent is: a modifier is loaded (by drip coating, spin coating, sputtering, etc.) on the side of carbon paper contacting the gas, and dried to obtain modified carbon paper, that is, a hydrophobic enhanced carbon paper substrate that can be used for a gas diffusion electrode is obtained; a suspension containing carbon black and a catalyst is loaded on the side of the carbon paper contacting the electrolyte by drip coating, spin coating, sputtering, etc., and dried to obtain a gas diffusion electrode.
[0022] The invention provides an application of the gas diffusion electrode in an electrolytic cell electrode and a battery electrode.
[0023] Beneficial Effects
[0024] The present invention utilizes ecological inorganic nanomaterials to hydrophobically modify carbon paper, constructs a rough and porous hydrophobic interface, improves gas diffusion electrode stability, reduces the use of binders, and ensures the electrochemical activity of catalysts. The commonly used hydrophobic modifier is polytetrafluoroethylene (PTFE) emulsion, which contains nonionic surfactants to stabilize the emulsion. The surfactant will dissolve in the electrolyte during actual use, and needs to be decomposed at 350 ° C or above, which is not applicable to unstable catalysts at high temperatures. The modification method of the present invention is simple and convenient, has low cost, and is fast to prepare. It is suitable for various metal-based catalysts to prepare gas diffusion electrodes. The obtained gas diffusion electrode has good hydrophobicity, and the hydrophobic surface contact angle can reach more than 150 °. At the same time, the hydrophobic layer will not cover the catalyst active site, and good catalytic performance can be maintained. The common water leakage and air leakage problems of gas diffusion electrodes are solved, and current stability can be maintained under high current.
[0025] The present invention uses fluorosilane as a modifier, and does not need to treat the surfactant in polytetrafluoroethylene at a high temperature above 350°C; in addition, the gas diffusion electrode prepared by the present invention can withstand a higher current density, and can achieve a high current density stable for 2000s under experimental conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A schematic diagram of the cross-sectional structure of a gas diffusion electrode according to an embodiment of the present invention;
[0027] Figure 2 The current-time diagram of the embodiment of the present invention and the comparative example at a constant potential of -1.0V. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0029] Example 1
[0030] Mix 10mL of deionized water and 50mL of ethanol, add 25% ammonia water to adjust the pH to 7.8, ultrasonically disperse for 20min, and stir at 500r / min for 20min at room temperature. Then add 3mL of tetraethyl orthosilicate, ultrasonically disperse for 1h, and stir at 500r / min for 6h at 35℃ to obtain the first solution. Mix 100mg of trishydroxymethylaminomethane with 65mL of deionized water, add 1mol / L concentrated hydrochloric acid to adjust the pH to 7.8, ultrasonically disperse for 30min, and stir at 500r / min for 30min at room temperature to obtain Tris-HCl buffer. Mix 150mg of dopamine hydrochloride with 50mL of Tris-HCl solution, ultrasonically disperse for 5min, and then stir at 500r / min for 12h at room temperature to obtain the second solution. Mix the first solution and the second solution in a volume ratio of 1.5mL:1mL, and stir at 1500r / min for 12h at 35℃ to obtain the third solution. 70 μL of perfluorooctyltrimethylsilane was added to the third solution, stirred at 35°C and 1500 r / min for 6 h, and then ultrasonicated for 30 min to obtain a hydrophobic agent. 2 The hydrophobic carbon paper was spin-coated and dried to a concentration of 2 mg / cm 2 The commercial copper nanoparticle suspension was spin-coated and dried to obtain a hydrophobically modified gas diffusion electrode.
[0031] Example 2
[0032] Mix 10mL ultrapure water and 60mL acetone, add 28% ammonia water to adjust the pH to 8, ultrasonically disperse for 20min, and stir at 500r / min for 20min at 15℃. Then add 3mL of tetraethyl orthosilicate, ultrasonically disperse for 1h, and stir at 500r / min for 6h at 15℃ to obtain the first solution. Mix 100mg of trishydroxymethylaminomethane with 80mL of deionized water, add 1mol / L concentrated hydrochloric acid to adjust the pH to 7.8, ultrasonically disperse for 30min, and stir at 600r / min for 30min at room temperature to obtain Tris-HCl buffer. Mix 150mg of dopamine hydrochloride with 50mL of Tris-HCl solution, ultrasonically disperse for 5min, and then stir at 600r / min for 12h at room temperature to obtain the second solution. Mix the first solution and the second solution in a volume ratio of 1.5mL:1mL, and stir at 1500r / min for 15h at 15℃ to obtain the third solution. 60 μL of perfluorobutyric acid was added to the third solution, and the mixture was sealed and stirred at 15°C for 8 hours, followed by ultrasonication for 40 minutes to obtain a hydrophobic agent. 2 The hydrophobic carbon paper was spin-coated and dried to a concentration of 2 mg / cm 2 The commercial copper nanoparticle suspension was spin-coated and dried to obtain a hydrophobically modified gas diffusion electrode.
[0033] Comparative Example 1
[0034] 2mg / cm 2 The copper catalyst suspension was spin-coated on the hydrophobic carbon paper and dried to obtain a gas diffusion electrode without hydrophobic modification. The gas diffusion electrodes prepared in Examples 1-2 and Comparative Example 1 were respectively electrolyzed in 1 mol / L KOH electrolyte for 2000 s. The current-time curves were as follows: Figure 2 As shown. It can be seen that the gas diffusion electrode prepared by hydrophobic modification of carbon paper using ecological inorganic nanomaterials has a higher reduction current at the same voltage, corresponding to a higher electrochemical activity, indicating that the hydrophobic treatment operation does not cover the catalytic sites. At the same time, its porous network structure allows gas to diffuse to the catalyst interface, promoting material transfer. And its current size basically does not fluctuate, corresponding to higher stability. In the comparative example, due to water and gas leakage on the electrode sheet, the bubbles seeping from the catalyst surface cover the active sites, resulting in drastic fluctuations in the current. The bubbles also promote the stripping of the catalyst, and the overall current decreases over time.
Claims
1. A method for preparing modified carbon paper, comprising: (1) mixing water and an organic solvent, adding a base to adjust the pH value, stirring, then adding ethyl silicate, stirring, to obtain a solution A; (2) mixing dopamine hydrochloride and Tris-HCl buffer, ultrasonicating and stirring to obtain solution B; (3) mixing solution A and solution B, then adding fluorosilane or perfluorocarboxylic acid, stirring, and ultrasonicating to obtain a modifier; (4) Loading the modifier on carbon paper and drying it to obtain modified carbon paper.
2. The preparation method according to claim 1, characterized in that: The organic solvent in step (1) is one or more of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, halogenated hydrocarbons, alcohols, ethers, esters, and ketones; wherein the aromatic hydrocarbon organic solvent includes one or more of benzene, toluene, and xylene; the aliphatic hydrocarbon organic solvent includes one or more of pentane, hexane, and octane; the alicyclic hydrocarbon organic solvent includes one or more of cyclohexane, cyclohexanone, toluene, and cyclohexanone; the halogenated hydrocarbon organic solvent includes one or more of chlorobenzene, dichlorobenzene, and dichloromethane; the alcohol organic solvent includes one or more of methanol, ethanol, and isopropanol; The ether organic solvent includes one or more of ether and propylene oxide; the ester organic solvent includes one or more of methyl acetate, ethyl acetate, and propyl acetate; the ketone organic solvent includes one or more of acetone, methyl butyl ketone, and methyl isobutyl ketone; the alkali is at least one of sodium hydroxide and ammonia water, wherein the mass percentage concentration of sodium hydroxide is 0.3%-0.4%, and the volume percentage concentration of ammonia water is 25-28%; the volume ratio of water, organic solvent, and tetraethyl orthosilicate is (10-20):(50-90):(3-5); the water is ultrapure water or deionized water.
3. The preparation method according to claim 1, characterized in that: In the step (1), alkali is added to adjust the pH value, ultrasonic dispersion is performed for 10-20 minutes, stirring is performed at 10-35° C. for 10-20 minutes, and then ethyl silicate is added, ultrasonic dispersion is performed for 0.5-1 hour, and stirring is performed at 10-35° C. for 3-8 hours.
4. The preparation method according to claim 1, characterized in that: In the step (2), the mass volume ratio of dopamine hydrochloride and Tris-HCl buffer is (10-200 mg): 50 mL; the pH of the Tris-HCl buffer is 7.8-9; The ultrasonic time in the step (2) is 1-5 min; the stirring is stirring at room temperature for 8-12 h.
5. The preparation method according to claim 1, characterized in that: In the step (3), the volume ratio of solution A to solution B is 0.1-(3:1); the fluorosilane is one or more of perfluorooctyltrimethylsilane, 1H, 1H, 2H, 2H perfluorododecyltriethoxysilane, tridecafluorooctylsilane, and heptadecafluorodecylsilane; the perfluorocarboxylic acid includes one or more of perfluorobutyric acid, perfluoropentanoic acid, perfluorohexanoic acid, perfluoroheptanoic acid, and perfluorooctanoic acid; the volume ratio of the fluorosilane or perfluorocarboxylic acid to tetraethyl orthosilicate is 1:(1-3); in the step (3), solution A and solution B are mixed and stirred at 10-35° C. for 5-15 h; in the step (3), stirring is performed at 10-35° C. for 5-12 h after adding the fluorosilane, and the ultrasonic time is 20-40 min.
6. The preparation method according to claim 1, characterized in that: The loading method in step (4) is at least one of drop coating, spin coating, and spraying; the loading amount of the modifier on the carbon paper is 0.1-30 μL / cm 2 .
7. A gas diffusion electrode prepared by the method according to claim 1, characterized in that: The electrode comprises the modified carbon paper according to claim 1, and a catalyst material supported on the modified carbon paper.
8. The gas diffusion electrode according to claim 7, characterized in that: The catalyst material is one or more of a metal-based catalyst and a non-metal-based catalyst; the metal-based catalyst includes one or more of copper, gold, silver, zinc, platinum and their compounds; the non-metal-based catalyst includes one or more of a protein and a small molecule catalyst; the catalyst material loading is 0.1-30 mg / cm 2 .
9. Use of the gas diffusion electrode according to claim 1 in electrolytic cell electrodes and battery electrodes.